External economic factors in the growth of the Peruvian economy: An autoregressive vector model (VAR) - Chávez Lazo, Iraida Betty (2021)
Objective: Determine the effect of external economic factors on Peru's economic growth in the period 2000-2019. Method: The investigation has a descriptive and explanatory nature, with a non-experimental design. The data collection technique employed the documentary analysis and used a census type population, considering the Peruvian and global economy. The Vector Autoregressive (VAR) model was estimated, from which a statistical and a structural analysis were developed. Results: It was found that the shock of the Chinese gross domestic product (GDP) reveals a growth in its participation (42,0%) on the growth of GDP in Peru in its 10th quarter. The shocks of the exchange terms registered an economic impact that fluctuates around 2,0% and the shocks of the country risk index have registered a slight increase, reaching 3,0% of the GDP variability of Peru. Conclusion: It was found that the variables considered as external factors, above all the China’s GDP, have repercussions, in one way or another, on the economic growth of the country.